Characterization of Co-Cr-Mo (F-75) alloy produced by solid state sintering - Zuraidawani, Che Daud; Shamsul Baharin, Jamaludin, Prof. Dr.; Md. Fazlul, Bari, Dr. (Trans Tech Publications, Switzerland, 2011)
Link to publisher's homepage at http://www.scientific.net/